Comparison of Laparoscopic Truncal Vagotomy And Gastrojejunostomy With Open Surgery For Pyloric Stenosis - Bhuiyan, Md Nur Hossain; Hossain, Md Nabir (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Peptic ulcer complication continues to inflict high morbidity. Surgery still remains the treatment of choice of peptic ulcer with Gastric Outlet Obstruction (GOO). With the advent of minimal access surgery laparoscopic truncalvagotomy with gastrojejunostomy is an attractive option. A selected group of patients may benefit more with laparoscopic than the open surgery. To evaluate the safety, efficacy and outcome of laparoscopic surgery for GOO in comparison with conventional laparotomy. Materials and methods: This is a retrospective study comparing Laparoscopic Truncal vagotomy and Gastrojejunostomy (LTVGJ) with open procedure. We excluded patients with severely malnutrition, age >60 years, malignancy, chronic hypertrophic pyloric stenosis, bleeding disorder, peritonitis, portal hypertension, jaundice, ASA >II. The study was performed on 30 patients who were clinically and radiologically diagnosed from June 2012 to June 2018. Out of them 15 patient were laparoscopically and 15 patients were done by laparotomy. Laparoscopic Truncal vagotmy and Gastrojejunostomy (LTVGJ) was done with ETS Flex 45 stapler. Operation technique, number of wound infection, post operative pain and hospital stay, early return to work were studied. Results: Thirty patients were studied, 28 male 2 female (Male to female ratio 9: 1) about 60% of the patients were within 3rd and 4th decade of age. Operation time was 120-180 minute, Only one patient had wound or port infection, 70% cases require less analgesic requirement than open surgery and hospital stay was 7 days. Conclusion: Laparoscopic truncal vagotomy with gastrojejunostomy is advantageous to open surgery by less postoperative pain, earlier return to normal diet, less wound infection, earlier discharge from hospital and early return to normal daily activity. Though it is costly, it offers excellent aesthetical results and may be considered as safe, effective and standard treatment option for selected patients. JCMCTA 2019 ; 30 (2) : 4-9